2004
DOI: 10.1258/135581904322987508
|View full text |Cite
|
Sign up to set email alerts
|

Use of, and attitudes to, clinical priority assessment criteria in elective surgery in New Zealand

Abstract: Variability in the use of CPAC tools meant that at the time of the study they did not provide a transparent and equitable method of determining access to surgery. This highlights the difficulties in developing and implementing CPAC and suggests that further development is difficult in the absence of evidence to identify patients who will benefit the most from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…This may cause frustration and resentment, compounding the original problem 25. There is an opportunity for family doctors to identify and address unmet needs and to support patients by advocacy in referral, by setting realistic expectations about management processes and by seeking a timely return to work where relevant 25 30. For patients awaiting diagnosis, practitioners may seek to identify and allay unfounded patient anxieties.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause frustration and resentment, compounding the original problem 25. There is an opportunity for family doctors to identify and address unmet needs and to support patients by advocacy in referral, by setting realistic expectations about management processes and by seeking a timely return to work where relevant 25 30. For patients awaiting diagnosis, practitioners may seek to identify and allay unfounded patient anxieties.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the use of a scoring system for prioritizing patients on waiting lists, although mandatory, was not followed by all the physicians. 40 Several reasons may exist. A mandatory system for prioritization may a.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the physician may see the system as a helpful tool when explaining to a patient why they have to wait a much longer time or why they do not need surgery. 40 Another explanation might be the reluctance of clinicians to use the scoring system on the grounds that it increases bureaucracy; however, in a pilot study, scoring a patient did not take more than 2-3 minutes. 41 Moreover, other health care professionals, such as nurses, could score the social criteria and leave the clinical criteria to the physicians to simplify the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The way in which surgeons reported using CPAC meant that in a "usual care" scenario the results were not likely to be consistent between surgeons [25]. There was considerable variation between surgeons and specialties in the way in which CPAC scores were constructed.…”
Section: Implementing the Elective Services Projectmentioning
confidence: 99%
“…There are a number of different versions of the same tools being used. Some tools consist of a five-point scale whereas others include specific scores for constructs such as severity (suffering; disability; clinical cost of delay) and ability to benefit (degree of improvement anticipated; likelihood of improvement) [25]. Tool scores are used in conjunction with financial thresholds, the score above which the relevant hospital is able to offer treatment given the funding available.…”
Section: Introductionmentioning
confidence: 99%